(untitled) (Orfeu, 2021)
In traditional piano teaching, the score is one of the main sources of information in the construction of musical knowledge. However, many of the ideas contained in the musical text may go unnoticed by the student, depending on the type of approach taken in reading the score. In this theoretical study, a creative way of exploring the musical text to be studied is proposed, using the conceptual map as a didactic resource, from a cognitive approach called Theory of Meaningful Learning. We understand that the use of the concept map: (1) emphasizes the student’s active posture in the process of learning music; (2) develops the ability to relate concepts extracted from the score; (3) increases the degree of awareness about the elements contained in the musical text; (4) stimulates the creative practices of representing musical concepts; (5) it generates positive links with the act of reading and decoding the score, forming the subunits. We hope that teachers, students and musicians will benefit from the wide possibilities of application of this simple and useful tool.